General pediatricians' competence in diagnosing children with autism - Maliwanag, Ma. Catalina B. (2007)
The importance of early and accurate diagnosis of autism cannot be overemphasized. This study determined general pediatricians' competence in diagnosing children with autism specifically on the areas of knowledge about the different aspects of autism, knowledge on the clinical manifestations of autism, and the ability to differentiate common developmental delays from autism. A 45-item questionnaire was given to 30 actively practicing general pediatricians in Quezon province. It was revealed that the general pediatricians are knowledgeable on the etiology and age onset of autism. Most of them do not use standardized tests in diagnosing and majority opt to refer the child to a developmental pediatrician for a definitive diagnosis. General pediatricians should be encouraged to participate in the Philippine Pediatric Society (PPS) Medical Home Initiatives, a family-centered, community-based partnership approach.
"October 2007."
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Pediaticians -- Philippines -- Quezon; Clinical competence -- Philippines; Autism in children -- Diagnosis; Autism in children -- Philippines -- Quezon